PENGARUH BEBAN TIDAK SEIMBANG TERHADAP EFISIENSI TRANSFORMATOR DAYA 2 X 500 kVA DI TERMINAL KARGO BANDARA JUANDA SURABAYA - Hartono, Hartono; Slamet Hariyadi; Rifdian Indrianto Sudjoko; Tekat Sukomardojo; Siti Julaihah (Jurnal Penelitian, 2024)
The problem of unbalanced load is something that is difficult to avoid in low voltage distribution networks even though the three-phase installation network is attempted with a balanced load distribution.... Unbalanced loads still occur because of the life and death of electrical appliances that alternate according to needs and things that are detrimental because in unbalanced loads flow neutral currents that cause power losses. In this study the authors examined two distribution transformers of 500 kVA each that supply the distribution network and low voltage installations in the cargo terminal building of Juanda Airport Surabaya. Ketentuyan on IEEE 446-1995 unbalanced load allowed is less than 20%, and after measurements, calculations and analysis on transformer number 01 cargo terminal with loading 27.73% - 28% there is no load development is still below 20% with efficiency 91, 06% - 96.5%, but on transformer number 02 with loading 10.58 5% - 12.14% there is an unbalanced load of 20% - 25.66% with efficiency 85.09% - 94.57%. Keywords: Unbalanced Load, Neutral Current, Power Loss, Efficiency